Pengolahan Ikan Lele Pembuatan Produk Nugget Ikan Lele - Ade putra; Tio Nadeak (Jurnal Pengabdian Dian Mandala, 2023)
This research is about how the use of catfish in making nuggets with the zero waste principle can be accepted or liked by the community and how much influence student innovation has on the economic value of processing catfish with the zero waste concept.